2022
DOI: 10.3390/s22030733
|View full text |Cite
|
Sign up to set email alerts
|

Target Localization in Wireless Sensor Networks Based on Received Signal Strength and Convex Relaxation

Abstract: A new positioning algorithm based on RSS measurement is proposed. The algorithm adopts maximum likelihood estimation and semi-definite programming. The received signal strength model is transformed to a non-convex estimator for the positioning of the target using the maximum likelihood estimation. The non-convex estimator is then transformed into a convex estimator by semi-definite programming, and the global minimum of the target location estimation is obtained. This algorithm aims at the L0 known problem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The simulation result shows that the maximum operational distance for the proposed array antenna’s beam gain is more than 25 m (m), whereas the minimum distance is also higher than 22 m (m), illustrated in Figure 14 . For the single ESPAR antenna gain 8.17 dBi, the distance is also higher than 17 m. Compared to the previously published papers beam gains, such as 7.99 dBi [ 13 ] and 6 dBi [ 24 ], the RSS result is also depicted in Figure 14 . It is shown that the distance due to the lower beam gain is less than the distance obtained due to the higher gain proposed antennas.…”
Section: Sir Improvement and Range Extensionmentioning
confidence: 80%
See 2 more Smart Citations
“…The simulation result shows that the maximum operational distance for the proposed array antenna’s beam gain is more than 25 m (m), whereas the minimum distance is also higher than 22 m (m), illustrated in Figure 14 . For the single ESPAR antenna gain 8.17 dBi, the distance is also higher than 17 m. Compared to the previously published papers beam gains, such as 7.99 dBi [ 13 ] and 6 dBi [ 24 ], the RSS result is also depicted in Figure 14 . It is shown that the distance due to the lower beam gain is less than the distance obtained due to the higher gain proposed antennas.…”
Section: Sir Improvement and Range Extensionmentioning
confidence: 80%
“…Different techniques could be used to find out the direction of tags; among them, beam scanning is an efficient method [ 1 , 13 , 15 , 47 ]. The ESPAR antenna cannot calculate the AoA of the incident beam by itself which is why it uses the beam scanning method as illuminated in Figure 9 a.…”
Section: Beam Scanning Methods (Bsm)mentioning
confidence: 99%
See 1 more Smart Citation
“…By utilizing an arithmetic optimization algorithm, the model aims to optimize the deployment of sensor nodes, which can potentially lead to improved localization performance. [4] addresses the problem of target localization in wireless sensor networks (WSNs) using received signal strength (RSS) measurements and convex relaxation techniques. The authors propose a method that estimates the location of a target based on the RSS values collected from multiple sensor nodes in the network.…”
Section: Related Workmentioning
confidence: 99%